Switzerland : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2012)
This Selected Issues Paper on Switzerland focuses on unprecedented currency appreciation and policy response. On September 6, 2011, the Swiss National Bank (SNB) surprised the market by explicitly committing to defending a floor of 1.20 on the exchange rate of EUR/CHF. The introduction of the floor was appropriate in light of the growth and deflationary risks and limited alternative policy options. From a global perspective, the SNB move may spark emulation by other countries experiencing appreciation pressures, but the specific circumstances of Switzerland may not be present elsewhere.